Effective doping of single-layer graphene from underlying SiO2 substrates - Shi, Yumeng (2011)
When a single-layer graphene (SLG) is on SiO2 substrates, the charge exchange at their interface results in a dipole, which direction strongly depends on the contact potential difference between the SLG and the